The Effectiveness of hydroalcoholic extract Hyssopus Angustifolius in amelioration of hematology and immune response indices in rat - Dehkordi, Mohsen Jafarian; Karimi-Dehkordi, Maryam; Emami , Maede; Gholami-Ahangaran, Majid (Acta Scientiarum. Animal Sciences, 2025)
Medicinal plants due to their diverse active ingredients have a high potential to become safe and effective drugs for humans and animals. One of the most important sources of medicinal plants in Iran is Hyssopus officinalis, which Hyssopus angustifolius (Hyssop) species is specific to Iran and grows in different parts of Iran. Numerous therapeutic properties of Hyssop such as antibacterial, antifungal, anti-inflammatory, and analgesic have been reported. However, there is limited information on its effects on the immune system. Therefore, the aim of this study was to investigate the effect of hydroalcoholic extract of Hyssop on blood and immunological parameters in Wistar rats, such as: complete blood cell count (packed cell volume, hemoglobin, red and white blood cells and percentage of each them), immunology parameters in blood (phagocytosis percentage and average phagocytic bacteria) and in serum (total protein, Albumin and Immunoglobulin M). For this purpose, 32 male Wistar rats were used. The rats were divided into a control and 3 experimental groups. The experimental groups received 50, 100 and 150 mg kg-1 of hydroalcoholic extract of Hyssop for 21 days. At the end of experiment period blood samples were taken to measure the blood and immunological parameters. The results showed that concentration of 50 mg kg-1 of the extract increased phagocytosis percentage, average phagocytic bacteria and increased immunity. A concentration of 100 mg kg-1 of Hyssop was led to an increase in blood Platelets. Also, this concentration was increased white blood cells and was decreased neutrophils and immunoglobulin M. Concentration of 150 mg kg-1 increased the level of immunity and number of white blood cells. In general, the results of this study showed that the effect of Hyssop on blood and immunological parameters is different depending on the type of indicator and Hyssop extract concentration.